Optimizing The Implementation Of Enterprise Resource Planning (ERP) In Company Financial Management - Hasanudin Hasanudin (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This research aims to optimize the application of the Enterprise Resource Planning (ERP) system in managing company finances. ERP is an integrated system that supports various business functions, including finance, by providing consistent and real-time data. This research uses a qualitative approach with descriptive methods. The research results show that ERP implementation requires thorough planning, active participation from stakeholders, effective training strategies, and monitoring the impact on post-implementation financial processes to ensure long-term success and optimal return on investment for the company. By implementing an ERP system in company financial management, it was found that this integration brings a number of significant benefits. It is proven that ERP simplifies financial processes, increases operational efficiency, and increases the accuracy of financial information by providing real-time access. In addition, ERP systems also provide benefits in terms of regulatory compliance and risk management, by enabling companies to proactively identify and manage financial risks.